1955
DOI: 10.1103/revmodphys.27.77
|View full text |Cite
|
Sign up to set email alerts
|

Energy Levels of Light Nuclei. V

Abstract: 1. He'(m m)He': E""=0. 95 (center of mass); mass defect = 12.92~0.05. 2. Li'(1 o)Hes: He'=He'+v+0. 97+0.05; mass defect = 12.94~0.05. 3. Li'(d He')He'. Qs --0.91&0. 09;mass defect= 12.85 0.09. 4. Li'(d o)He'. Qs --14.23&0.07; mass defect= 12.85 0.07. We adopt: He' mass defect=12. 92&0.08 Mev. I. (a) H'(d n)He4 Q =17.577 Zs 16. 63--(b) H'(1 e)He4The yield exhibits a pronounced maximum near E~=107 kev, with a cross section of 4.95&0.14 b (Ar 54) t Lsee also (Aj 52c)). Precise cross sections in the tange 8&=10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
3

Year Published

1955
1955
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(33 citation statements)
references
References 655 publications
1
28
1
3
Order By: Relevance
“…Figure 4 shows the cross section curve plotted beside an energy level diagram (from Ajzenberg and Lauritsen 1955). Since Ajzenberg and Lauritsen's review paper, Almqvist, Allen, and Bigham (1955) have reported a previously unobserved level at 9·2 MeV.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the cross section curve plotted beside an energy level diagram (from Ajzenberg and Lauritsen 1955). Since Ajzenberg and Lauritsen's review paper, Almqvist, Allen, and Bigham (1955) have reported a previously unobserved level at 9·2 MeV.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…A summary of these experiments is given by . Ajzenberg and Lauritsen (1955). Experiments on the photodisintegration of DBe have, with one exception, used monochromatic.…”
mentioning
confidence: 99%
“…In the experiments reported here, the cross section of 6Li(n,3H)4He was measured, with good energy resolution, over a neutron energy range 2 ·0-2 . 65 MeV; this corresponds to an excitation of the compound 7Li system from 9·0 to 9 ·55 MeV where a fairly well-established level of 7Li is known to be present (Ajzenberg and Lauritsen 1955). From a knowledge of the neutron and triton partial widths which have been established for this level by y-ray absorption experiments it would appear that, to an order of magnitude, the resonance cross section to this level by neutron absorption in 6Li should be several hundred millibarns.…”
Section: Discussionmentioning
confidence: 99%
“…The 7Li(p, r)8Be reaction has a Q-value of 17 ·242 MeV (Ajzenberg and Lauritsen 1955). The ground state of 8Behas a width of a few electron-volts, which is small enough to be ignored, and so the photons from transitions to the ground state have energy given by (1).…”
Section: Principle Of Experimentsmentioning
confidence: 99%
“…160(y, n) 15 0 EXPERIMENT Because of the small cross section of this reaction and the low intensity of y-radiation available, it was necessary to detect the 15 0 produced with the highest possible efficiency. This was done by counting the 1·68 MeV positrons emitted by 15 0, the half-life of which is 118 sec (Ajzenberg and Lauritsen 1955). 47t geometry was obtained by making a scintillation counter in which the scintillator itself was rich' in oxygen.…”
Section: Principle Of Experimentsmentioning
confidence: 99%